الأمراض والأوبئة المعدية في الدولة العثمانية: دراسة على القرن التاسع عشر - محمد، أحمد صالح علي (مركز جمعة الماجد للثقافة والتراث - قسم الدراسات والنشر والشؤون الخارجية, 2021)
This study deals with research of the history of infectious diseases in the Ottoman Empire during the nineteenth century AD. Since those epidemics swept the Ottoman lands, they have killed many people due to the lack of experience in dealing with these rapidly spreading deadly diseases. The study showed the rapid impact and spread of these diseases and epidemics as the Ottoman Empire was keen to maintain several measures and procedures to reduce them and because it overlooked global trade routes such as land routes from the side of the Indian subcontinent, the Mediterranean Sea and the Red Sea. Moreover, these seas were very important for the state, global trade and the movement of passengers and travelers. It was necessary to control these roads, whether land or sea, impose preventive measures and precautionary measures, and detect these diseases and epidemics.
Keywords: الأمراض المعدية -- الأوبئة المعدية -- المناخ الحار -- المستنقعات المائية -- الدولة العثمانية